MONITORING DAN ANALISIS MESIN 3D PRINTING BERBASIS SENSOR GETARAN UNTUK MENGOPTIMALKAN KUALITAS HASIL - Ikhwan Taufik; Herianto Herianto; M. K. Herliansyah (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2018)
Today, printing technology not only talking about paper, plastic, and the other flat media. Printing technology can make a three dimensional object like the picture at the soft file. Mostly, the printing technology is used to create or print a prototype object and object that is not mass-produced. The application of 3D printing technology can be found in industry, health, architecture, fashion, and even food. This research raises one of the techniques of 3D Printing technology. That is Fused Deposition Modeling (FDM) which applies Material Extrusion process to build a three dimensional product. The material is filament made of thermoplastic material, metal wire, and other. The filament is inserted into the extruder part (extrusion head nozzle in 3D Printing machine) and melted by heating. Models are produced by extrusion of material streams that form layers and re-harden immediately. Extrusion process in making the model of the material will certainly cause a movement and vibration caused by the printing process is running. This article presents the results of vibration measurements on a 3D printer machine and the result of measuring the surface roughness level on the specimens of the printing process using a 3D printer C01. The Type is cartesian. In addition, this study aims to study and analyze the amount of vibration generated during the printing process takes place. It is associated with the impact that occurs on the quality of printing. With the monitoring during the printing process, it is expected to predict the level of quality of the printing results more early. However, the results of the measurements in this study was not seen any significant influence. The visible vibration is just on the X axis. Surface Roughness measurements for the first specimen, the specimens with 50% printing speed have an average surface roughness level of = 8,6485 μm. Specimens with 100% printing speed have an average surface roughness level of = 8.2893 μm. Specimens with 200% printing speed have an average surface roughness level of = 7.864 μm.